1970
DOI: 10.2172/4751944
|View full text |Cite
|
Sign up to set email alerts
|

Waste Solidification Program. Volume 5. Phosphate Glass Solidification Performance During First Radioactive Tests in Waste Solidification Engineering Prototypes.

Abstract: m o n s t r a t i o n r u n s i n WSEP a t t h e P a c i f i c Northwest L a b o r a t o r y . R a d i o a c t i v i t y p r o c e s s e d was i n c r e a s e d from350,000 c u r i e s i n t h e f i r s t r u n t o 2 , 4 0 0 , 0 0 0 c u r i e s i n t h e s i x t h r u n .The s e l f -g e n e r a t i n g h e a t r a t e w i t h i n e a c h r e c e i v e r w a s t e w i t h i n a f u l l 8-inch d i a m e t e r p o t r e p r e s e n t e d 1 . 3 t o n n e s of power r e a c t o r f u e l ( i r r a d i a t e d a t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
1978
1978

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The major development of phosphate waste glasses started at Brookhaven National Laboratory (Tuthill, 1967) and culminated in the manufacure of 11 canisters of radioactive phosphate waste glass during the Waste Solidification Engineering Prototypes (WSEP) program at PNL (McElroy, 1970;McElroy, 1971). The WSEP program showed that phosphate glass had several shortcomings when compared with silicate glasses.…”
Section: Glass-ceramic Waste Glassesmentioning
confidence: 99%
“…The major development of phosphate waste glasses started at Brookhaven National Laboratory (Tuthill, 1967) and culminated in the manufacure of 11 canisters of radioactive phosphate waste glass during the Waste Solidification Engineering Prototypes (WSEP) program at PNL (McElroy, 1970;McElroy, 1971). The WSEP program showed that phosphate glass had several shortcomings when compared with silicate glasses.…”
Section: Glass-ceramic Waste Glassesmentioning
confidence: 99%
“…The tests were p a r t of a comprehensive program sponsored by t h e U. S. Atomic Energy Commission t o develop' s a f e r methods f o r p e r p e t u a l s t o r a g e o f h i g h l y r a d i o a c t i v e wastes. Other s o l i d i f i c a t i o n p r o c e s s e s i n v e s t i g a t e d i n t h e United S t a t e s a s p a r t of t h i s program i n c l u d e d t h e a g i t a t e d t r o u g h c a l c i n e r , ( 2 ) t h e ceramic sponge p r o c e s s , ( 3 ) t h e r o t a r y b a l l k i l n c a l c i n e r , ( 4 ) t h e f l u i d i z e d bed c a l c i n e r , ( 5 ) t h e p o t c a l c i n e r , (6) and t h e phosphate g l a s s p r o c e s s . ('I The l a t t e r t h r e e p r o c e s s e s have been developed u n t i l t h e y are I n t h e e a r l y developmental p e r i o d , a m e l t e r w a s c l o s ecoupled t o t h e r a d i a n t h e a t s p r a y c a l c i n e r .…”
Section: S O L I D I F I C a T I O N Of Two O T H E R Waste T Y P E Smentioning
confidence: 99%
“…The ( 5 ) where 3 % of t h e ruthenium p r e s e n t i n t h e e v a p o r a t o r accumulated i n t h e f r a c t i o n a t o r bottoms.…”
Section: A U X I L I a R Y E V A P O R A T O R S I N C E T H E Accumumentioning
confidence: 99%